Durability properties of fibrillated polypropylene fibre reinforced high performance concrete - Maruthachalam, D.; Gurunathan, M.; Padmanaban, I.; Vishnuram, B.G. (Journal of Structural Engineering, 2024)
The aim of the study is to investigate the strength and durability properties of “Fibrillated Polypropylene Fibre Reinforced High Performance Concrete” FPPFRHPC. The effect of addition of fly ash and metakaolin as mineral admixtures and addition of Fibrillated Polypropylene Fibre for the production of FPPFRHPC was studied in detail. The investigation was carried out on the HPC containing Fibrillated Polypropylene Fibre at the various proportions of 0, 0.1, 0.2 and 0.3 percentages by the volume fraction. The Portland cement was partially replaced with mineral admixtures by fly ash 10% and metakaolin 10%. The FPPFRHPC mix, grade M60 concrete is designed as per ACI 211.4R-08. In the present experimental investigation, the effect of strength properties on durability properties were studied through the measurement of permeable voids and water absorption, acid attack / resistance and permeability test. The results indicated that on the strength studies of 10% fly ash and 10% metakaolin mineral admixtures with addition of 0.3% of FPP Fibre (FMHPC3 mix) showed improved performance, although fibres do not significantly improve strength, but has reduced number of cracks and crack width. The mix FMHPC3 shows better performance on durability studies, when compared with other mixes. The investigation reveals that addition of FPPF makes the concrete more durable along with the mineral admixtures.